An Investigation of Foam Concrete Usability as a Cavity Filler Material in Mining - KÖMÜRLÜ, Eren (GeoScience Engineering, 2021)
Strength and deformability properties of different cavity filler materials of a phenolic foam, a polyurethane based foam and a foam concrete (FC) mix were investigated and compared in this study. Instead of using polymeric foam fillers, FC usage was found to supply better load bearing capacity and modulus of elasticity values. The fresh FC mixes consisting of cement, water and foaming agents are able to be filled into the mine cavities. In the cavity filling applications, typical polymer foams cause support reactions with low stiffnesses and let the rock mass at the roof to be loosened. A relatively stiff cavity filling material can help rock masses to bear itself by prevention of the loosening. To avoid excessive deformations of the rock masses, the deformation modulus is an important parameter as well as the strength property. The FC filler materials were found advantageous because of economical supply of improved load bearing capacities and stiffness values for controlling the rock mass convergences.